7(z+11)=4(z+11)

Simple and best practice solution for 7(z+11)=4(z+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(z+11)=4(z+11) equation:


7(z+11)=4(z+11)

We simplify the equation to the form, which is simple to understand
7(z+11)=4(z+11)

Reorder the terms in parentheses
+(+7z+77)=4*(z+11)

Remove unnecessary parentheses
+7z+77=+4+*(+z+11+)

Reorder the terms in parentheses
+7z+77=+(+4z+44)

Remove unnecessary parentheses
+7z+77=+4z+44

We move all terms containing z to the left and all other terms to the right.
+7z-4z=+44-77

We simplify left and right side of the equation.
+3z=-33

We divide both sides of the equation by 3 to get z.
z=-11

See similar equations:

| 3X^2-20x+15=0 | | -15+16+19d=20+19d | | 12(2x-9)=4(6x+6) | | 6x-17=4x+31 | | (-87)+x=-25 | | 0=8v-8v | | 2(3k+7)+12(2+k)=-16 | | -3x+6x=-12+4x-5x | | 0.06/18 | | -16q+7=-16q-2 | | 38+x=82 | | 11a=24+8a | | -2-4-3b=-6-10b | | 7x+6=7(x-7) | | -10c-10=2-8c | | -5n-8=1-8n | | 9f=10+9f | | 6n-8(n+5)=-70 | | -4-8n+8n=n+3 | | -7m+m-4=-6m+5 | | 6(x+1)/5=5x-5 | | 7x+5=2x+1 | | -x+41+8x-9=-3 | | 0.40x+0.45(20)=0.20(35) | | -10t=-10t+9 | | 4(3y-2)/7=3y-5 | | 7(x-4)=4x-16 | | 1.6x=.8x | | 2/7x+3/7=-1/7 | | 5-7x=50-42x | | 5+9k=-k-5 | | -15-5m=-6m+6m |

Equations solver categories